The Idea of a ‘Just City’ – a Concept of an Aggregate Measure of Development in Polish Cities - Antczak, Elżbieta; Rzeńca, Agnieszka; Sobol, Agnieszka (Bulletin of Geography. Socio-economic Series, 2023)
The subject of the article is the ‘just city’ concept. Justice, greening and making cities productive in the long term are the main axes of the integrated development of modern cities. The main goal of the paper is to discuss and assess the degree of justice in the development of 66 Polish cities with poviat rights in 2010, 2015, 2018, and 2020. Based on previous research and available data, an aggregate measure of a just city is proposed. A dynamic method of zero unitarization is used. The analysis shows that between 2010 and 2020, there was an increase in the level of justice in urban development (the average yearly rate of change was 2.5%). Only seven cities recorded a decline. There was also a slight and decreasing variation in cities in terms of the urban justice. One can even speak of an equalization of inequality here.